After restraint stress, mice with high and low immobility time have a different neurochemical and behavioral profile - Reis-Silva, Thiago; Lima, Ana Paula; Moreira, Natalia; Calefi, Atilio; Sandini, Thaísa Meira; Florio, Jorge Camilo; Bernardi, Maria Martha (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2016)
High and low immobility on the tail suspension test is a common tool for assessing antidepressant drug effects. However, those parameters might be a natural phenotype present in the mice population and could be selected through behavior evaluation without an induced-drug behavior need. High immobility has been also related to depressed-like behavior, that in humans are characterized by wide range of symptoms, such as anhedonia, anxiety and tiredness.